Pengaruh Model Pembelajaran Scramble Berbantuan Media Puzzle Terhadap Penguasaan Kosakata Siswa Kelas I SDN Gugus 1 Kecamatan Gerung - Ginanda Azahra Va Arni; Nurul Kemala Dewi; Arif Widodo (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
This study aims to determine the effect of the Scramble learning model assisted by Puzzle media on the language acquisition of first grade students at SDN Gugus 1, Gerung District. The population of this research was all of the first grade students at SDN Gugus 1, Gerung District, totaling 218 students. The sample in this study were 44 students who were determined by the Placement Test. This type of research is a Quasi Experiment with the Nonequivalent Control Group Design type. Data collection is done by testing. Data analysis used Anakova with a significance level of 0.05. The Anakova test results obtained a value of 0.023 <0.05 which indicated that Ha was accepted and H0 was rejected. Based on this, it can be interpreted that the Scramble learning model assisted by Puzzle media has a positive effect on the vocabulary mastery of first grade students at SDN Gugus 1, Gerung District. In addition to increasing vocabulary mastery using the Scramble learning model for students assisted by Puzzle media, it also increases student learning activities